(untitled) (Biological Sciences - PJSIR, 2010)
Tardive dyskinesia (TD), an involuntary orofacial hyperkinetic disorder, is the major limitation of neuroleptic therapy. Role of 5-hydroxytryptamine (5-HT; serotonin) may be important in the treatment of schizophrenia and TD. Rats chronically treated with haloperidol exhibiting vacuous chewing movements (VCMs) with tongue protrusions and facial musculature are widely used as animal model of TD. Rats repeatedly injected with haloperidol at the dose of 1 mg/mL/kg twice a day for 2 weeks displayed VCMs that increased in a time dependent manner as the treatment was continued for 5 weeks. VCMs were produced two days after withdrawal; animals were given meta-chlorophenylpiperazine (m-CPP) challenge (3 mg/mL/kg) to monitor the responsiveness of 5-HT2C receptors. The intensity of m-CPP induced hypophagia was more in repeated haloperidol + m-CPP injected rats after 4 h but not after 2 h post m-CPP challenge. m-CPP also attenuated haloperidol induced increased dopamine (DA) and 5-HT metabolism both in dorsal and ventral striatum. However, these effects were more pronounced in ventral striatum. Results are discussed in context with responsiveness of 5-HT2C receptors. Findings may help in extending the therapeutics in schizophrenia.